KEDUDUKAN KREDITUR SELAKU PENERIMA JAMINANA FIDUSIA DALAM HAL DEBITUR PAILIT MENURUT UU NO.37 TAHUN 2004 TENTANG KEPAILITAN - MUHAMMAD ARIEF (JURNAL CIVIL LAW USU, 2013)
Abstrak : Fiduciary Creditor receiver position is as a Preferred Lender. This right is not clear because of the bankruptcy or liquidation of the Borrower Lender Fiduciary. Preferred Creditors (Secured Creditors) in Bankruptcy Creditors usually called Separatists. Creditor Beneficiary Creditor Fiduciary Separatists very concerned as it may execute their rights as to avoid bankruptcy. Regulations in the field of Law and Bankruptcy Fiduciary current was less provide legal protection against creditors Recipient Fiduciary. Method of approach used in this thesis is legal. Based on the research results penulisn is in Article 56 of Law no. 37 of 2004 on Bankruptcy states that the rights of creditors separatist execution as referred to in Article 56 Paragraph (1) of the Bankruptcy Act is suspended for a period not exceeding 90 (ninety) days from the date of declaration putuisan bankruptcy. If the verification meeting beralrut-soluble and future insolvency be delayed beyond a period of 90 (ninety) days after the decision of bankruptcy, creditor's rights can begin to implement the separatists to become involved pending execution. This poses a risk to the creditors of the insured fiduciary considering the goods as collateral in the form of movable property is no longer on debitors Keywords: The debtor, creditor, fiduciary, Bankruptcy